Primary hepatic neuroendocrine tumour masquerading as a giant haemangioma: an unusual presentation of a rare disease. Issue 9 (8th September 2020) - Almas, Talal; Inayat, Faisal; Ehtesham, Maryam; Khan, Muhammad Kashif
Abstract : Primary hepatic neuroendocrine tumour is an exceedingly rare entity. We hereby delineate the case of a 45-year-old Balti descent woman who hails from a land-locked village situated in the foothills of the Pakistani Himalayas. The patient presented to our medical centre with a hepatic mass. She underwent extensive diagnostic workup. The consistent findings of an abdominal CT scan, coupled with her clinical history, insinuated a preoperative diagnosis of atypical hepatic haemangioma. After a detailed discussion in a multidisciplinary meeting, a standard right hemihepatectomy was performed. She had an uneventful postoperative recovery and was discharged in stable condition after 1 week. Surprisingly, pathological examination and immunohistochemistry of the resected specimen divulged the diagnosis of a grade II primary hepatic neuroendocrine tumour. Her somatostatin-receptor scintigraphy and Gallium-68 DOTATATE positron emission tomography scan excluded residual hepatic or additional body lesions. Regular follow-ups over the past 4 years demonstrated unremarkable radiological findings with no recurrence to date.